Textualist Islam vis-à-vis Dynamic Islam: A Study of the Urgency of the Dominance of Inclusive Narratives in the Digital Space - Azisi, Ali Mursyid; Rifa'i, Ahmad; Mufidah, Harini Nur; Nuroniyah, Zulfatin (Universitas Islam Negeri Raden Intan Lampung, 2023)
The textualist group, since the presence of social media as a form of technological progress, has changed platforms in spreading its exclusive understanding, or even plunged into extreme doctrinal actions. However, on the other hand, there is dynamic Islam with the same vision spreading its ideology and teachings which are more inclined towards moderate, inclusive and tolerant movements. This article attempts to analyze the importance of the dominance of the moderate Islamic narrative as a bulwark for Indonesian society so that it is not exposed to textualist Islamic circles who tend to legalize violence in the name of religion, are conservative, extreme and even non-tolerant. Textualist Islam is represented by Hizbut Tharir Indonesia and Salafi-Wahabi, while the moderate actor is Nahdlatul Ulama. The method used is qualitative descriptive analysis, with the steps of writing literature and media studies. The findings of this article are that implementing inclusive narratives in the digital space is by applying the values of religious moderation, by creating inclusive, creative and interesting content, collaboratively, and continuously. In this way, it is able to create an expansion of the area of dominance of inclusive narratives on various digital media platforms. This effort is a form of religious actualization that is rahmatan lil 'alamin and maintains diversity from divisions in the name of religion.